2023
DOI: 10.1038/s41467-023-37357-4
|View full text |Cite
|
Sign up to set email alerts
|

Tackling antibiotic resistance by inducing transient and robust collateral sensitivity

Abstract: Collateral sensitivity (CS) is an evolutionary trade-off traditionally linked to the mutational acquisition of antibiotic resistance (AR). However, AR can be temporally induced, and the possibility that this causes transient, non-inherited CS, has not been addressed. Mutational acquisition of ciprofloxacin resistance leads to robust CS to tobramycin in pre-existing antibiotic-resistant mutants of Pseudomonas aeruginosa. Further, the strength of this phenotype is higher when nfxB mutants, over-producing the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 80 publications
(177 reference statements)
0
18
0
Order By: Relevance
“…It remains unclear whether this difference is specific to cystic fibrosis or whether there are other contexts in which efflux pump mutants survive in the host. To address scenarios in which efflux pump upregulation does prove to be prevalent, it will be interesting to explore the potential benefits of antibiotic cycling or combinations as a means to exploit these mutants’ collateral sensitivity to other antibiotics 63 , 64 .…”
Section: Discussionmentioning
confidence: 99%
“…It remains unclear whether this difference is specific to cystic fibrosis or whether there are other contexts in which efflux pump mutants survive in the host. To address scenarios in which efflux pump upregulation does prove to be prevalent, it will be interesting to explore the potential benefits of antibiotic cycling or combinations as a means to exploit these mutants’ collateral sensitivity to other antibiotics 63 , 64 .…”
Section: Discussionmentioning
confidence: 99%
“…In clinical isolates, TFR mutations lead to the de-repression of their targets ( 27 ), some of which are efflux transporters, thus contributing to AMR and adjusting to changing environments ( 28 ). NfxB mutants are commonly found in ciprofloxacin-resistant P. aeruginosa clinical strains ( 29 , 30 ). Previous structural studies on several TFRs have revealed that the arginine residue in the HTH domain is in direct contact with the DNA phosphate backbone ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…For P. aeruginosa biofilms, a final inoculum of 1 × 10 4 colony-forming units (cfu) mL –1 was added to the polycarbonate disk and incubated statically for 24 h at 37 °C before treatment. , For polymicrobial biofilms, a final inoculum of 1 × 10 5 cfu mL –1 for C. albicans and 1 × 10 6 cfu mL –1 for S.…”
Section: Methodsmentioning
confidence: 99%